2021
DOI: 10.5152/dir.2020.19654
|View full text |Cite
|
Sign up to set email alerts
|

MRI quantification techniques in fatty liver: the diagnostic performance of hepatic T1, T2, and stiffness measurements in relation to the proton density fat fraction

Abstract: N onalcoholic fatty liver disease (NAFLD) is one of the most common causes of chronic liver disease, with an estimated worldwide prevalence of around 25% (1). It may range from simple steatosis, which is considered a benign condition, to nonalcoholic steatohepatitis (NASH), which can progress to fibrosis, cirrhosis, liver failure, and hepatocellular carcinoma. NAFLD is also known to be associated with metabolic syndrome, which is a risk factor for cardiovascular disease and type II diabetes mellitus (2-4).The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…lww.com/HEP/H132). Both cT1 and T1 measure a mixed signal from water and fat in the liver, [30,31] and have a potential bias from the partial volume effect of steatosis. [32] Consequently, T1 is significantly associated with PDFF measurements in NAFLD/NASH.…”
Section: Discussionmentioning
confidence: 99%
“…lww.com/HEP/H132). Both cT1 and T1 measure a mixed signal from water and fat in the liver, [30,31] and have a potential bias from the partial volume effect of steatosis. [32] Consequently, T1 is significantly associated with PDFF measurements in NAFLD/NASH.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with high BMI, elevated VFA has a more signi cant correlation with insulin resistance and MAFLD with brosis, which is consistent with these studies 18,19 . Erden A showed that VFA values has a strong correlation with the liver fat content 20 . As we all known, liver fat is considered to be a kind of ectopic fat and connected to the liver through the portal vein in anatomically.…”
Section: Discussionmentioning
confidence: 99%
“…However, this method yields a slightly higher hepatic fat content than liver histology[ 59 ] and the accuracy of measurements could be affected by fibrosis and severe steatosis. It lacked the power to detect the changes in non-alcoholic fatty liver disease (NAFLD) such as inflammation or fibrosis[ 13 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that MR elastography and T1-T2 mapping can be useful in detecting hepatic inflammatory and fibrotic changes[ 13 , 60 , 61 ]. Therefore, the multiparametric MRI protocol may be helpful in liver tissue characterization and in risk stratification and therapeutic management of patients with NAFLD.…”
Section: Discussionmentioning
confidence: 99%